Assessment of Some Serum Liver Parameters among Sudanese Adult Cigarette Smokers, Omdurman City, Sudan (2019) - Modawe, GadAllah; Ahmed, AbdelAzim Alsanousi; Abdelsalam, Kamal Eldin Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Backgrounds: Cigarette smoke contains a large number of chemical substances with hepatotoxic potential including nicotine. Many researchers have reported that, the relationship between cigarette smoker and liver injury. Objectives: The objective of this study was to investigate the serum liver function tests among Sudanese adult cigarette smokers. Methods: This study was an analytical case control study, carried out in Omdurman city, 100 subjects enrolled in the study matched for age and sex, 50 cigarette smokers as case group, with their age ranged between 18 to 43 years and the mean age was 24 years, and also 50 non smokers as control group, all study parameters estimated using spectrophotometric methods. Results: The (mean ± SD) serum total proteins, albumin, total bilirubin, AST, ALT and ALP levels in cigarette smokers and non smokers respectively were (6.63±9.14g/L, 3.37±4.11g/L, 0.66±0.15mg/dL, 26.66±8.46 IU/L, 19.00±8.89 IU/L, 157.84±17.43 IU/L), (6.90±6.21g/L, 3.45±2.78g/L, 0.55±0.16 15mg/dL, 23.50±4.95 IU/L, 13.91±5.33 IU/L, 146.67±11.52 IU/L). There was statistically significant difference (P<0.05) between serum ALP, ALT and total bilirubin levels between smokers and control subjects. The age had a positive correlation with serum bilirubin, serum ALT and serum ALP respectively (r=0.387, p=0.006, r=0.393, P=0.005, r=0.0318, p=0.025). Conclusion: Cigarette smokers had a significant increase in serum ALP, ALT and total bilirubin levels. This study also revealed a positive correlation between age and serum total bilirubin, ALT and ALP. المستخلص                                                                                                                     الخلفية : يحتوي دخان السجائر على عدد كبير من المواد الكيميائية الضارة للكبد مثل مركب النيكوتين, و قد أورد عدد من الباحثين بأن هنالك علاقة واضحة بين التدخين و أمراض الكبد. أهداف البحث : كان هدف هذه الدراسة هو فحص وظائف الكبد في دم مدخني السجائر السودانيين البالغين. الطرق المتبعة :  كانت هذه الدراسة دراسة تحليلية وصفية محكمة للحالات المرضية, أجريت في مدينة أمدرمان؛ و احتوت على 100 متطوع متوافقين في العمر و الجنس، 50 منهم مدخنين كمجموعة حالة للبحث تتراوح أعمارهم بين 18 و 43 سنة وبمتوسط عمر 24 سنة، بينما 50 منهم كانوا غير مدخنين كمجموعة تحكم للبحث. كل فحوصات البحث قد أجريت باستخدام قياس الطيف الضوئي. النتائج : تم أخذ المتوسط الحسابي ±الانحراف المعياري لمعدلات الدم لكل من البروتين، الالبيومين، البيليروبين الكلي،الفوسفاتاز القلوي (ALP)،ناقلة امين الالانين(ALT)، ناقلة امين الاسباراتات (AST)، و التي كانت في مصل دم المدخنين بالترتيب كالآتي (6.63±9.14 جم/ل، 4.11±3.37جم/ل، 0.66±0.15ملجم/دسل، 26.66±8.46 وحدة دولية / لتر، 19± 8.89وحدة دولية / لتر، 157.84 ± 17.43وحدة دولية / لتر)، و كانت في مصل دم غير المدخنين كالآتي (6.9±6.21 جم/ل، 3.45 ± 2.78 جم/ل، 0.55±0.16 ملجم/دسل، 23.5±4.95 وحدة دولية / لتر، 13.91±5.33وحدة دولية / لتر،146.67±11.52 وحدة دولية / لتر). كان هناك فرق ذو دلالة إحصائية (P <0.05) بين ALP، ALT ومستويات البيليروبين الكلية بين المدخنين والأشخاص الغير مدخنين.كان للسن علاقة إيجابية مع مصل الدم لكل من البيليروبين، ALT و ALP على التوالي (r=0.387، p=0.006، r=0.393، P=0.005، r=0.0318، p=0.025). الخلاصة : كان في دم مدخني السجائر زيادة كبيرة في مستويات ALP و ALT ومستوى البيليروبين الكلي. كما كشفت هذه الدراسة أيضا وجود علاقة إيجابية بين العمر و البيليروبين الكلي ، ALT و ALP.